Three-body Faddeev calculation for 11Li with separable potentials - Ueta, K.; Miyake, H.; Bund, G. W. [UNESP] (American Physical Soc, 1999)
The halo nucleus 11Li is treated as a three-body system consisting of an inert core of 9Li plus two valence neutrons. The Faddeev equations are solved using separable potentials to describe the two-body interactions, corresponding in the n-9Li subsystem to a p1/2 resonance plus a virtual s-wave state. The experimental 11Li energy is taken as input and the 9Li transverse momentum distribution in 11Li is studied. [S0556-2813(99)01703-3].